236 Omental Fat Torsion Masquerading Clinically as Acute Appendicitis in a Young Male Patient: A Rare Aetiology of Acute Abdomen and The Value of Diagnostic Laparoscopy. (12th October 2021) - Abuelgasim, M; Baggaley, A; Saad, E
Abstract: Acute abdominal pain is a common surgical presentation and acute appendicitis remains the top differential for most young adults. Omental fat torsion has emerged as a rare aetiology of an acute surgical abdomen in the younger population that closely mimics acute appendicitis in its clinical presentation. Preoperative diagnosis is extremely challenging in this age group due to the rarity of the condition and the non-specific nature of its clinical and laboratory findings, and hence most reported diagnoses were made intra-operatively. We report a case of omental fat torsion in a 22-year-old male who presented with clinical features that were highly suggestive of acute appendicitis. However, the diagnostic laparoscopy revealed a normally looking appendix and terminal ileum, with the presence of a twisted segment of the greater omentum in the right lumbar region. A laparoscopic omentectomy and a prophylactic appendectomy to prevent furture acute appendicitis were performed with an uneventful postoperative recovery. Histology confirmed omental fat infarction and a normal appendix. This reported case highlights a rare cause of right iliac fossa pain and demonstrates the value of diagnostic laparoscopy in the context of clinically suspected acute appendicitis in younger male patients. Diagnostic imaging was not deemed necessary in our patient given the strong clinical suspicion of acute appendicitis. Prompt laparoscopy led to definitive diagnosis as well as treatment and avoided the radiation exposure necessitated during a diagnostic computed tomography scan.